Rudolf Otto and the concept of holiness - Raphael, Melissa (Clarendon, 1997)
An examination of Rudolf Otto's 20th-century concept of holiness. This volume analyzes the scholarly context that shaped Otto's idea of holiness, and discusses the relation of the numinous and the holy to the divine personality, morality religious experience and emancipatory theology.